2016
DOI: 10.1080/23120053.2016.1128147
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective comparison of cytological and histological bone marrow morphology in adult antiretroviral-naïve and antiretroviral experienced human immunodeficiency virus-infected patients with peripheral blood cytopaenias

Abstract: A cohort of human immunodeficiency virus (HIV)-positive patients presenting to a quaternary hospital in KwaZulu-Natal, South Africa over a period of one year was identified and morphological analyses of their bone marrow aspirates and trephine biopsies (BMAT) undertaken. Aim: To compare and contrast the bone marrow morphological features of antiretroviral (ARV)-naïve and ARV-experienced HIV-positive population with cytopaenias; correlate the findings with CD4 counts; and, draw conclusions on whether ARV are as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 20 publications
(25 reference statements)
0
4
0
Order By: Relevance
“…15,16 Cytopenias are well documented, multifactorial complications of HIV infection. 4,5 Our study demonstrated that 46% of HIV-positive participants had one or more forms of cytopenia: anaemia, pancytopenia, bicytopenia and thrombocytopenia. A study conducted in Uganda demonstrated that 65% of antiretroviral-therapynaïve HIV-positive participants had a form of cytopenia.…”
Section: Discussionmentioning
confidence: 72%
See 3 more Smart Citations
“…15,16 Cytopenias are well documented, multifactorial complications of HIV infection. 4,5 Our study demonstrated that 46% of HIV-positive participants had one or more forms of cytopenia: anaemia, pancytopenia, bicytopenia and thrombocytopenia. A study conducted in Uganda demonstrated that 65% of antiretroviral-therapynaïve HIV-positive participants had a form of cytopenia.…”
Section: Discussionmentioning
confidence: 72%
“…For this reason our study reported low rates (4/120) of tuberculosis diagnosis on BMAT when compared to other South African studies that demonstrated higher tuberculosis diagnoses on BMAT samples. 4,14 These studies included: a study that looked at 410 case samples of adult and paediatric BMAT submitted for excluding tuberculosis, which showed a 32.5% tuberculosis prevalence, and a study that assessed bone marrow morphology in 74 patients, in which comparing morphology between patients on antiretroviral therapy and patients naïve to antiretroviral therapy showed a 31% tuberculosis prevalance. 4,14 Both of these studies had higher tuberculosis prevalence due to their study populations being cases with high risk for tuberculosis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations